Asymmetric Impact of El Niño‐Southern Oscillation on Autumn Accumulated Cyclone Energy Over the Western North Pacific - Jinjie Song; Philip J. Klotzbach; Na Wei; Yihong Duan (Geophysical Research Letters)
Abstract This study investigates the asymmetric response of accumulated cyclone energy (ACE) of western North Pacific (WNP) tropical cyclones during autumn (September–November) to El Niño‐Southern Oscillation (ENSO) from 1970 to 2023. Although basinwide ACE is positively correlated with ENSO, it significantly decreases in La Niña but only slightly changes in El Niño. This is mainly due to a significant reduction (weak change) in basinwide TC genesis but also a southeastward (northwestward) shift in El Niño (La Niña). This leads to longer‐tracked (shorter‐tracked) storms in El Niño (La Niña). Furthermore, in El Niño years, ENSO‐related signals migrate farther eastward, leading to the regions suppressing TC genesis being much larger than those favoring TC genesis. By comparison, in La Niña years, ENSO‐related signals extend more westward, while the TC‐favoring regions are of a similar size to the TC‐suppressing regions. Finally, El Niño is primarily responsible for the asymmetric autumn ENSO‐ACE relationship.